Multi-lane Roundabout Capacity Evaluation - Šarić, Ammar; Lovrić, Ivan (Frontiers in Built Environment, 2017)
Although two-lane roundabouts theoretically exhibit excellent operating performance, in practice, safety problems arise because of inappropriate driving behavior. Turbo roundabouts, which are characterized by a much higher level of safety, are alternatives to classic two-lane roundabouts, but the capacity-related benefits derived from such roundabouts remain an open issue. Accordingly, this study uses an equilibrium traffic flow allocation approach to evaluate multi-lane roundabout capacity based on gap acceptance theory. Capacity levels are calculated and compared for different gap acceptance parameters, including local parameters, and different traffic flow scenarios. It is found that the capacity of minor approaches on turbo roundabouts is always higher than on two-lane roundabouts, but that the main approaches on two-lane roundabouts exhibit better performance in terms of fully equilibrium traffic allocation. This state, however, cannot be achieved for every demand scenario. The results depend strongly on traffic movements and gap acceptance parameters indicating the need for local calibration processes.